2022
DOI: 10.1007/s13555-022-00875-y
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Disparities in Atopic Dermatitis in Latin America: A Narrative Review

Abstract: Introduction Atopic dermatitis (AD) is a chronic, pruritic skin disease caused by a mixture of genetic, immunological, and environmental factors, characterized by periods of inflammation and remission. In Latin America (LA), the prevalence of AD ranges up to 25% in children and 1–3% in adults. The natural history of the disease for most patients is that AD goes into remission in adolescence and adult life. Only 10–30% of patients continue to have symptoms of the disease in adulthood. There are pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 75 publications
1
20
0
Order By: Relevance
“…In Latin American (LA) countries, economic conditions may limit access to some therapies, leading AD specialists to choose the best available and accessible treatment, which may not always be the preferred one. 7 , 8 , 9 For example, in Ecuador, Paraguay, and Cuba, access to therapies such as biologicals and small molecules is limited due to their unavailability or high cost to patients. Additionally, access to medical consultation is limited in some LA populations due to geographical conditions, health system restrictions, or sociocultural aspects, making it difficult to apply recommendations and conduct adequate medical follow-up.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Latin American (LA) countries, economic conditions may limit access to some therapies, leading AD specialists to choose the best available and accessible treatment, which may not always be the preferred one. 7 , 8 , 9 For example, in Ecuador, Paraguay, and Cuba, access to therapies such as biologicals and small molecules is limited due to their unavailability or high cost to patients. Additionally, access to medical consultation is limited in some LA populations due to geographical conditions, health system restrictions, or sociocultural aspects, making it difficult to apply recommendations and conduct adequate medical follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Most accepted recommendations for AD diagnosis and treatment management are based on studies involving European and North American populations, with few clinical trials including LA patients. 7 , 8 , 9 Despite this, most local guidelines in LA replicate the recommendations of the European and North American guidelines, with little consideration of regional aspects. The SLAAI 15 , 17 has considered various regional characteristics, including sociodemographic factors and access to diagnostic tests and treatment, when making recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allergists and dermatologists generally make up a small proportion of medical doctors in North America, as well as developing countries [ 39 ]. Croce et al [ 40 ] found that caregivers believed their child's atopic dermatitis to be under better control when receiving care of a dermatologist.…”
Section: Disparities In Skin Diseases: Atopic Dermatitis Chronic Spon...mentioning
confidence: 99%